HUBUNGAN FAKTOR LINGKUNGAN TERHADAP PRODUKSI SERASAH MANGROVE TELING TOMBARIRI, TAMAN NASIONAL BUNAKEN - Langi, Martina A.; Nurmawan, Wawan (RISALAH KEBIJAKAN PERTANIAN DAN LINGKUNGAN Rumusan Kajian Strategis Bidang Pertanian dan Lingkungan, 2023)
This study aims to compare ecosystem productivity based on litter production rate associated with tree species and climate parameters in the Teling Tombariri Mangroves, Bunaken National Park, North Sulawesi. Litter collection was carried out for 12 months in the three main mangrove constituent zones, the litter was then analyzed based on fraction and type. Litter production was then correlated with rainfall, ambient temperature, and humidity using a simple correlation coefficient. Linear correlations between monthly litter production of leaf, twig, fruit-flower fractions (reproductive fraction) of each mangrove species and monthly climate parameters (temperature, rainfall, and humidity) were calculated using Pearson's correlation p